Research on the Implementation of Chinese Excellent Traditional Culture Education for Preschool Children Based on OBE - Tian, Hua (Pacific International Journal, 2026)
This study addresses the integration of Chinese Excellent Traditional Culture (CETC) into preschool education, a critical initiative for fostering cultural identity and values from an early age. Despite growing policy emphasis, practical implementation in kindergartens often remains superficial, hindered by outdated pedagogical methods, insufficient teacher training, and a lack of systematic, child-centered models. The primary objectives of this research are to: (1) diagnose the current challenges and deficiencies in CETC education at the preschool level; (2) propose an innovative, outcomes-based talent training model for preschool educators; and (3) develop practical strategies for effective cultural integration. Employing a mixed-methodology approach—including action research, surveys, and interviews with 121 teachers, 210 children, and parents at Xiangyu Kindergarten—the study identifies key issues such as over-reliance on rote methods, limited teacher cultural literacy, and misalignment with children's developmental needs. The findings underscore the necessity of a paradigm shift towards a student-centered, Outcomes-Based Education (OBE) framework. The proposed model emphasizes reverse curriculum design, differentiated instruction, home-kindergarten collaboration, and situated, life-oriented evaluation. This research concludes that a systematic, professionally developed approach to CETC in preschools can significantly enhance educational quality, ensure meaningful cultural transmission, and contribute to the holistic development of young learners.